Synthesis of Phenanthrenes via Palladium-Catalyzed Three-Component Domino Reaction of Aryl Iodides, Internal Alkynes, and o-Bromobenzoic Acids - Yang, Yuzhong; Zhou, Liwei; Yang, Xiumei; Luo, Xiai; Deng, Guobo; Yang, Yuan; Liang, Yun (Synthesis, 2020)
A new palladium-catalyzed domino alkyne insertion/C–H activation/decarboxylation sequence has been developed, which provides an efficient approach for synthesizing a variety of functionalized phenanthrenes in moderate to good yields. The method shows broad substrate scope and good functional group tolerance by employing readily available materials, including aryl iodides, internal alkynes, and o-bromobenzoic acids, as three-component coupling partners.
Keywords: phenanthrenes; domino reaction; C–H activation; decarboxylation; palladium-catalyzed